Kartu Tantangan Permainan: Tinjauan Sistematis tentang Gamifikasi untuk Keterampilan Dasar Bola Voli - Nasrullah, Nasrullah; Santoso, Januar Abdilah; Jusuf, Jeane Betty Kurnia (Jurnal Porkes, 2025)
The incorporation of gamification elements in physical education signifies a pedagogical advancement capable of improving student engagement and skill acquisition. This systematic literature review evaluates the efficacy of Game Challenge Cards as a gamification tool for enhancing volleyball abilities in elementary school children. In accordance with PRISMA criteria, we conducted a systematic analysis of 35 peer-reviewed articles published from 2018 to 2025, sourced from the Scopus, Web of Science, ERIC, and SportDiscus databases. The results indicate that gamification methods employing challenge cards substantially improve the acquisition of essential volleyball abilities (impact sizes between d=0.52-0.87), elevate student motivation (assessed by validated measures), and foster inclusive learning settings. Game Challenge Cards exhibit efficacy via organized visual guidance, incremental skill enhancement, prompt feedback systems, and recognition of accomplishments. The efficacy of implementation is influenced by aspects such as design quality, integration into broader pedagogical frameworks, and teacher preparation. This review adds to the expanding evidence supporting gamification in physical education and offers physical educators research-based techniques to improve volleyball instruction in elementary environments. Future research directions encompass the examination of long-term skill retention, the exploration of digital-physical integration possibilities, and the investigation of tailored applications for distinct student populations.